A study on the fire propagation characteristics in large-opening multi-level limestone mines in Korea. Issue 6 (1st November 2016) - Lee, Changwoo; Nguyen, Vanduc
Abstract: Recently, deployment of large-capacity diesel haulage trucks is rapidly increasing in the domestic large-opening limestone mines due to the high level of operational flexibility. However, in multi-level mines, this trend has raised the serious concern for the risk of diesel vehicle fire. Fire in a deep multi-level mine site is harder to control and likely to develop into disastrous results. Developing the emergency evacuation strategies and controlling the fire should presuppose a knowledge of the fire behavior in mines. This paper aims at studying the behavior of a 25-ton diesel truck fire showing approximately the maximum heat release rate of 30 MW by computational fluid dynamic analysis. Spatial and temporal distributions of the hot air stream, smoke layer, and CO gas layer in multi-level mine sites are evaluated, and the effects of fan operation are scrutinized to find the appropriate fan location and operating mode. In addition, several other aspects of the fire development such as backlayering and throttling effects are also studied. The ultimate goal is to provide fundamental information about fire propagating characteristics in multi-level large-opening underground limestone mines for developing the mine fire evacuation plan and protect the workers' safety.